(untitled) (Biological Sciences - PJSIR, 2022)
Skipper fauna of Balochistan province is not properly studied. To fill this gap, a study was conducted to explore the skipper’s fauna from previous literature and new collection from Balochistan, Pakistan. We report 21 species of skippers from two subfamilies, Coeliadinae and Hesperiinae. Out of 21 species five species namely Hesperia comma (Linnaeus, 1758), Parnara guttatus (Bremer and Grey, 1852), Pyrgus cashmirensis Moore (1874), Pyrgus darwazicus Grum-Grshimailo (1890) and Pyrgus sidae (Esper, 1784) under subfamily Hesperiinae are recorded for the first time from Balochistan. Out of five reported species from Balochistan, two species Pyrgus darwazicus and Pyrgus sidae are new records for Pakistan.